Influence of Reaction Conditions on Lignin Hydrothermal Treatment - Erdocia, Xabier; Prado, Raquel; Corcuera, M. Ángeles; Labidi, Jalel (Frontiers in Energy Research, 2014)
Organosolv lignin, obtained from olive tree pruning under optimised conditions, was subjected to a hydrothermal depolymerisation process catalysed by sodium hydroxide. The depolymerisation of lignin was carried out at 300 ºC using different reaction times (20, 40, 60, 70, 80, 90 and 100 min) in order to study the influence of this parameter on lignin depolymerisation. The resulting products (oil and residual lignin) were measured and analysed by different techniques (GC/MS, HPSEC and pyrolysis-GC/MS) in order to determine their nature and composition. Coke was also formed, at a lower quantity, incompetitive repolymerisation reactions during the lignin hydrothermal treatment. The maximum oil yield and concentration of monomeric phenolic compounds was obtained after80 min of reaction time. The highest reaction time studied (100 min) had the worst results with the lowest oil yield and highest coke production.